2004
DOI: 10.1074/jbc.m400568200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Factor Xa-interactive Site within Residues 337–372 of the Factor VIII Heavy Chain

Abstract: We recently demonstrated that the residues 337-372, comprising the acidic C-terminal region in A1 subunit, interact with factor Xa during the proteolytic inactivation of factor VIIIa (Nogami, K., Wakabayashi, H., and Fay, P. J. (2003) J. Biol. Chem. 278, 16502-16509). We now show this sequence is important for factor Xa-catalyzed activation of factor VIII. Peptide 337-372 markedly inhibited cofactor activation, consistent with a delay in the rate of cleavage at the A1-A2 junction. Studies using the isolated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 36 publications
2
36
0
2
Order By: Relevance
“…Thus, whereas similar exosite interactions facilitate formation of the enzyme-substrate complexes, the sites for tethering appear to differ significantly. This contention is further supported by our observation that the 373-395 peptide blocked thrombin-catalyzed cleavage of isolated heavy chain, whereas this peptide showed no effect on factor Xa-catalyzed proteolysis (32). Furthermore, we observed that thrombin and factor Xa demonstrated markedly different reactivities toward cleaving the Arg 740 -Ser 741 scissile bond in the factor VIII D392A/D394A mutant.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Thus, whereas similar exosite interactions facilitate formation of the enzyme-substrate complexes, the sites for tethering appear to differ significantly. This contention is further supported by our observation that the 373-395 peptide blocked thrombin-catalyzed cleavage of isolated heavy chain, whereas this peptide showed no effect on factor Xa-catalyzed proteolysis (32). Furthermore, we observed that thrombin and factor Xa demonstrated markedly different reactivities toward cleaving the Arg 740 -Ser 741 scissile bond in the factor VIII D392A/D394A mutant.…”
Section: Discussionsupporting
confidence: 72%
“…Mechanistic studies of factor Xa-catalyzed proteolysis of factor VIII heavy chain indicated that the proteinase interacts with acidic residues localized within the 337-372 region separating the A1 and A2 domains to facilitate cleavages at both Arg 372 and Arg 740 (32). Furthermore, this binding utilizes the heparin-binding exosite of factor Xa (63).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic peptide corresponding to factor VIII residues 337-372 was prepared by Quality Controlled Biochemicals, Inc. (Hopkinton, MA). Biotinylated peptide was prepared using sulfo-NHSbiotin as described previously (17). The B-domainless factor VIII expression construct RENeo factor VIII and baby hamster kidney cells were gifts kindly provided by Dr. Pete Lollar.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we demonstrated recently that the 337-372 acidic region following the A1 domain, in particular a cluster of amino acid residues 361-363, contributes to a unique factor Xa-interactive site within the factor VIII heavy chain (17). Factor Xa also interacts with these residues in the A1 subunit, possibly via the heparin-binding exosite of this protease (18), and this binding modulates cleavage at Lys 36 (11).…”
mentioning
confidence: 98%